Novel gamebook Frasa-Satu Bayangan: Kajian mengenai sudut pandangan / Muhammad Azri Mohd Yusof - Mohd Yusof, Muhammad Azri (Faculty of Education, 2013)
This study is about the usage of point of view in a literature Gamebook entitled FRASA: Satu Bayangan by Muhammad Azri Bin Mohd Yusof. The objective of the study is to ensure that the storyline presented in the novel employs one or more the point of view that exists. There are the first person point of view, the second person point of view and the third person point of view. This study also shows the difference between FRASA: Satu Bayangan with other novels. Therefore, this study directed to the used of Gamebook concept which is a genre of book or novel nowadays. Concurrently, this study will investigate the usage of Narratology theory to choose the point of view and the narrative. The study uses a qualitative method as the model study by analyzing the content of novel and Gamebook.